NR4A Expression by Human Marginal Zone B-Cells - Kim Doyon-Laliberté; Josiane Chagnon-Choquet; Michelle Byrns; Matheus Aranguren; Meriam Memmi; Pavel Chrobak; John Stagg; Johanne Poudrier; Michel Roger (Antibodies, 2019)
We have previously characterized a human blood CD19+CD1c+IgM+CD27+CD21loCD10+ innate-like B-cell population, which presents features shared by both transitional immature and marginal zone (MZ) B-cells, named herein “precursor-like” MZ B-cells. B-cells with similar attributes have been associated with regulatory potential (Breg). In order to clarify this issue and better characterize this population, we have proceeded to RNA-Seq transcriptome profiling of mature MZ and precursor-like MZ B-cells taken from the blood of healthy donors. We report that ex vivo mature MZ and precursor-like MZ B-cells express transcripts for the immunoregulatory marker CD83 and nuclear receptors NR4A1, 2, and 3, known to be associated with T-cell regulatory (Treg) maintenance and function. Breg associated markers such as CD39 and CD73 were also expressed by both populations. We also show that human blood and tonsillar precursor-like MZ B-cells were the main B-cell population to express elevated levels of CD83 and NR4A1-3 proteins ex vivo and without stimulation. Sorted tonsillar precursor-like MZ B-cells exerted regulatory activity on autologous activated CD4+ T-cells, and this was affected by a CD83 blocking reagent. We believe these observations shed light on the Breg potential of MZ populations, and identify NR4A1-3 as potential Breg markers, which as for Tregs, may be involved in stabilization of a regulatory status. Since expression and activity of these molecules can be modulated therapeutically, our findings may be useful in strategies aiming at modulation of Breg responses.